2018
DOI: 10.1080/01658107.2017.1409770
|View full text |Cite
|
Sign up to set email alerts
|

Blepharospasm in Japan: A Clinical Observational Study From a Large Referral Hospital in Tokyo

Abstract: Focal dystonia is regarded as a characteristic feature of blepharospasm. However, patients do not always present with motor symptoms. To clarify the clinical features of blepharospasm in Japan, we conducted a retrospective observational study involving a large population of patients from a single institution. Common symptoms included difficulty opening the eyes, photophobia, and ocular pain/irritation. Initial symptoms often occurred following the long-term use of psychotropics such as etizoram, benzodiazepine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Twenty-one reported median age at onset in 5–6th decade, with an overall weighted average of 56 ± 6 years ( Figure 2B ). Six reported diagnosis was significantly delayed; two of these revealed that only about half of the patients received the correct diagnosis within one year [ 4 , 10 ]. The median time from onset to diagnosis was 2 years in one study [ 22 ] and the weighted mean from three other studies was 46 ± 68 months [ 7 , 11 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty-one reported median age at onset in 5–6th decade, with an overall weighted average of 56 ± 6 years ( Figure 2B ). Six reported diagnosis was significantly delayed; two of these revealed that only about half of the patients received the correct diagnosis within one year [ 4 , 10 ]. The median time from onset to diagnosis was 2 years in one study [ 22 ] and the weighted mean from three other studies was 46 ± 68 months [ 7 , 11 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, its varied presentations are often not appreciated, and it is probably under-diagnosed. Several reports describe frequent misdiagnoses [ 5 , 7 , 10 ]. Initial diagnostic accuracy was only 19% in one study [ 10 ] and 10% in another [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been several reports of this symptom since ancient times 20 - 24 . In a recent study, Wakakura et al 25 conducted a retrospective observational study involving a large population of patients from a single institution, and reported the need to remain aware of “benzodiazepine-induced ophthalmopathy” when prescribing etizolam, BZ drugs, and zolpidem (= Z-drug). Therefore, when switching from BZ to Z-drugs, it is essential to pay close attention to “benzodiazepine-induced ophthalmopathy” as Ocular signs and symptoms NEC.…”
Section: Discussionmentioning
confidence: 99%